Cryptography as the Phenomenon of Russian Literature Language (12 - S.V. Zapechnikov (Bezopasnostʹ Informacionnyh Tehnologij, 2011)
Prescientific methods of text securing are not solitary in the Ancient Russian literature. Ancient Russian ciphertexts have been investigated before mainly as the elements of political, diplomatic, military history or as the elements of Slavonic literature process. In this paper we consider ciphertexts as the facts of history of Russian literature. Our research shows that cryptography was an element of language mentality for Ancient Russians. Comparing to modern ciphers, it was not used only as the technical and mathematical method.